Penerapan Nilai-Nilai Anti Koruptif sebagai Pembentukan Karakter Mahasiswa yang Berpancasila - Maria Anjelina Odje; Paulina Dhiu; Kornelina Rima Demo; Maria Karolina Tena; Maneldis Romana Ngode; Kristiana Owa Kaju (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the application of anti-corruption values ini shaping students’ character based on Pancasila principles. The study employs a qualitatitive descriptive method, where data is collected through literature reviews. The literature used in this research includes scientific articles related to the application of anti-corruption values in forming Pancasila-oriented student character. Data collection was carried out by exploring articles from electronic journals and other publications related to the topic. The results of the study indicate that the integration of anti-corruption education into the academic curriculum influences students’ ethical awareness and behavior. Moreover, the implementation of values such as honesty, justice, and responsibility supports the development of character aligned with Pancasila values.